2014
DOI: 10.1248/cpb.c14-00451
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Brinzolamide Drug–Resin <i>in Situ</i> Thermosensitive Gelling System for Sustained Ophthalmic Drug Delivery

Abstract: In this study a brinzolamide drug-resin ophthalmic thermosensitive in situ gelling system was developed and evaluated. Brinzolamide was combined with ion exchange resins to prolong the retention time of drugs in the eye and to reduce ocular and systemic side effects. Poloxamer F127 was used as gelling vehicle in combination with carbopol 934P, which acted as a viscosity-enhancing agent. They were prepared using the cold method. The optimized formulation exhibited a sol-gel transition at 33.2 1.1°C with pseudop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…T gel of the sol-gels were measured through the magnetic stirring method as described previously ( Li et al, 2014 ). The sol-gels (F1-F8) were diluted with simulated tear fluid (STF) at 6:1 (v/v) ratio.…”
Section: Methodsmentioning
confidence: 99%
“…T gel of the sol-gels were measured through the magnetic stirring method as described previously ( Li et al, 2014 ). The sol-gels (F1-F8) were diluted with simulated tear fluid (STF) at 6:1 (v/v) ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Drugs release slow along with the gel to achieve the purpose of sustained-release. The in vitro process of thermo sensible in situ gel form of many drugs indicated that the release of this drug could sustain 4 ~ 7 days [23,28,29], which highly accorded with the medication cycle (3 ~ 5 days) in veterinary clinical application.…”
mentioning
confidence: 87%
“…34 Briefly, six healthy New Zealand White rabbits were chosen and divided into BH-solution and Mt-BH-LP groups. Samples (50 µL) were dropped into conjunctival sacs of rabbits, and then the eyes were closed for 1 minute.…”
Section: In Vivo Precorneal Retention Of Mt-bh-lpsmentioning
confidence: 99%